Effect of the Etching Duration and Ultrasonic Cleaning on Microtensile Bond Strength Between Feldspathic Ceramic and Resin Cement - Leite, Fabiola Pessoa; Oezcan, Mutlu; Valandro, Luiz Felipe; Cunha Moreira, Carlos Heitor; Amaral, Regina [UNESP]; Bottino, Marco Antonio [UNESP]; Kimpara, Estevão Tomomitsu [UNESP] (Taylor & Francis Ltd, 2013)
This study assessed the effect of different etching durations of feldspathic ceramic with hydrofluoric acid (HF) and ultrasonic cleaning of the etched ceramic surface on the microtensile bond strength stability of resin to a feldspathic ceramic. The research hypotheses investigated were: (1) different etching times would not affect the adhesion resistance and (2) ultrasonic cleaning would improve the adhesion. Ceramic blocks (6 x 6 x 5 mm) (N = 48) were obtained. The cementations surfaces were duplicated in resin composite. The six study groups (n = 8) were: G1Etching with 10% aqueous HF (30 s) + silane; G 210% HF (1 min) + silane; G3-10% HF (2 min) + silane; G4-10% HF (30 s) + ultrasonic cleaning (4 min) in distilled water + silane; G5-10% HF (1 min) + ultrasonic cleaning + silane; G6-10% HF (2 min) ultrasonic cleaning + silane. The cemented blocks were sectioned into microbars for the microtensile test. The etching duration did not create significant difference among the groups (p = .156) but significant influence of ultrasonic cleaning was observed (p = .001) (Two-way ANOVA and Tukey's test, p > 0.05). All the groups after ultrasonic cleaning presented higher bond strength (19.38-20.08 MPa) when compared with the groups without ultrasonic cleaning (16.2117.75 MPa). The bond strength between feldspathic ceramic and resin cement was not affected by different etching durations using HF. Ultrasonic cleaning increased the bond strength between ceramic surface and resin cement, regardless of the etching duration.
Keywords: Acid etching; Adhesion; Feldspathic ceramic; Hydrofluoric acid; Microtensile bond strength; Ultrasonic cleaning